How is the gastroesophageal reflux disease prevalence, incidence, and frequency of complications (stricture/esophagitis/Barrett’s esophagus/ carcinoma) in Turkey compared to other geographical regions globally? - Bor, Serhat; Sarıtaş Yüksel, Elif (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Bor S, Sarıtaş Yüksel E. How is the gastroesophageal reflux disease prevalence, incidence, and frequency of complications (stricture/ esophagitis/Barrett’s esophagus/carcinoma) in Turkey compared to other geographical regions globally? Turk J Gastroenterol 2017;28(Suppl 1); S4-S9 Full Text Turkish